Asesmen Online sebagai Asesmen Alternatif dalam Pembelajaran Era Digital: Penelitian Systematic Literature Review - Adelia Alfama Zamista (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2022)
Education in the digital era is characterized by the rapid flow of information exchange due to the integration of information and communication technology (ICT) in the educational process. In the digital era, learning assessments are carried out with the help of ICT, so the term online assessment is known. This literature study uses a systematic literature review (SLR) method, which consists of 6 stages: planning, literature review, inclusion and exclusion criteria, quality assessment, data collection, and data analysis. This study aims to determine the reasons for implementing online assessments, the types of online assessments, and the advantages of online assessments. The results of data analysis show that in Indonesia, the Covid-19 pandemic and the development of ICT have triggered the implementation of online assessments. There are various online assessments implemented by teachers, ranging from assessments to test knowledge using various applications such as Quizizz and Google Forms to assessments for attitude skills such as online self-assessments. One of the advantages of implementing an online assessment is its ability to provide feedback quickly following the characteristics of education in the digital era.